2007
DOI: 10.1053/j.gastro.2007.07.025
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 Transgenic Mice Exhibit Enhanced MDP-Mediated Down-Regulation of TLR2 Responses and Resistance to Colitis Induction

Abstract: Background and Objectives-Mutations in the CARD15 gene affecting NOD2 function are susceptibility factors in Crohn's disease. We set out to explore the mechanism of this susceptibility using mice that over-express NOD2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 26 publications
4
76
0
Order By: Relevance
“…For example, a frameshift mutation in the NOD2 gene is associated with Crohn's disease, an autoimmune disease associated with severe inflammation of the bowel mucosa (14,27). Evidence suggests that lack of bacterial sensing by the mutant NOD2 in individuals with Crohn's disease contributes to the pathology of disease (36,39). A loss of surveillance activity by NOD2 may result in the inability of local responses in the intestinal mucosa to control bacterial infection, thereby initiating systemic responses and leading to aberrant inflammation.…”
mentioning
confidence: 99%
“…For example, a frameshift mutation in the NOD2 gene is associated with Crohn's disease, an autoimmune disease associated with severe inflammation of the bowel mucosa (14,27). Evidence suggests that lack of bacterial sensing by the mutant NOD2 in individuals with Crohn's disease contributes to the pathology of disease (36,39). A loss of surveillance activity by NOD2 may result in the inability of local responses in the intestinal mucosa to control bacterial infection, thereby initiating systemic responses and leading to aberrant inflammation.…”
mentioning
confidence: 99%
“…Furthermore, we recently found that NOD2-transgenic mice expressing NOD2 under the control of class II promoter or administered a plasmid expressing NOD2 manifest decreased susceptibility to TNBS colitis (21). These findings led us in the present study to determine whether administration of MDP protects mice from experimental colitis.…”
Section: Administration Of Mdp Protects Mice From Tnbs Colitis We Prmentioning
confidence: 82%
“…for 3 consecutive days beginning at the time of colitis induction (days 0, 1, 2), but in this case each MDP dose was accompanied by i.p. administration of either intact CARD15, frameshift CARD15, or control empty vector encapsulated in hemagglutinating virus of Japan (HVJ) for efficient in vivo delivery (21). As shown by the weight curves in Figure 5A and the histologic data in Figure 5B, while MDP injection protected NOD2-deficient mice reconstituted with intact CARD15 plasmid, it did not protect NOD2-deficient mice reconstituted with frame-shift CARD15 plasmid or with control empty plasmid.…”
Section: Figurementioning
confidence: 99%
“…NOD2 KO mice demonstrate exacerbated cell trafficking responses into the iris, cell infiltration into the vitreous, and cytokine production. This observation suggests that NOD2 may serve differential roles in the eye to either promote or temper inflammation, which would be akin to the intestine wherein NOD2 exerts a role in suppressing inflammation triggered by PGN and other TLRs in the context of colitis [62][63][64]. Studies conducted in our own lab have found an involvement of the NOD2-RIP2 pathway in the protection of the eye to PGN (Figure 1).…”
Section: Short Communicationmentioning
confidence: 93%